Concentrate-roughage ratios in pelleted rations for fattening lambs. Three mgs. Stilbestrol implants and/or cobalt bullets for lambs fed pelleted rations - Menzies, C.S.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
One hundred fifty-white faced New Mexico wether lambs were used. Lambs were shorn and drenched with phenothiazine before starting on test. Two weeks after the lambs arrived from the range an outbreak of coccidiosis occurred. Approximately half of the lambs were treated with sulfa-drugs. November 30, about five weeks after lambs arrived from range, they were weighed, divided into six lots of 22 lambs each, and self fed.
Keywords: Sheep; Stilbestrol implant; Cobalt bullets; Pelleted rations